The Fecal Microbiota Is Already Altered in Normoglycemic Individuals Who Go on to Have Type 2 Diabetes - Wang, Li; Yu, Xinwen; Xu, Xiaoqiang; Ming, Jie; Wang, Zhifeng; Gao, Bin; Xing, Ying; Zhou, Jie; Fu, Jianfang; Liu, Tao; Liu, Xiangyang; Garstka, Malgorzata A.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: Mounting evidence has suggested a link between gut microbiome characteristics and type 2 diabetes (T2D). To determine whether these alterations occur before the impairment of glucose regulation, we characterize gut microbiota in normoglycemic individuals who go on to develop T2D. Methods: We designed a nested case-control study, and enrolled individuals with a similar living environment. A total of 341 normoglycemic individuals were followed for 4 years, including 30 who developed T2D, 33 who developed prediabetes, and their matched controls. Fecal samples (developed T2D, developed prediabetes and controls: n=30, 33 and 63, respectively) collected at baseline underwent metagenomics sequencing. Results: Compared with matched controls, individuals who went on to develop T2D had lower abundances of Bifidobacterium longum, Coprobacillus unclassified, and Veillonella dispar and higher abundances of Roseburia hominis, Porphyromonas bennonis, and Paraprevotella unclassified. The abundance of Bifidobacterium longum was negatively correlated with follow-up blood glucose levels. Moreover, the microbial KEGG pathways of carbohydrate metabolism, methane metabolism, amino acid metabolism, fatty acid metabolism, and membrane transport were changed between the two groups. Conclusions We found that fecal microbiota of healthy individuals who go on to develop T2D had already changed when they still were normoglycemic. These alterations of fecal microbiota might provide insights into the development of T2D and a new perspective for identifying individuals at risk of developing T2D.